Self-adjustment phenomena among high school students: The role of coping strategy and parenting style - Alif Muarifah; Intan Hashimah Mohd Hashim; Dian Ari Widyastuti (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
Self-adjustment is one of the social skills that individuals urgently need. Self-adjustment helps individuals build social relationships positively with others, groups, and their environment. This study aimed to explore the factors that influence self-adjustment, both internal and external factors. Participants in this study were 116 grade XI high school students in Yogyakarta selected with proportional random sampling. The instruments in this study were the self-adjustment scale, problem-focused coping scale, emotional-focused coping scale, authoritarian parenting style scale, authoritative parenting style scale, and permissive parenting style scale. Multiple linear regression was used to analyze the data. The findings indicate highly significant relationships between coping strategies, parenting style, and self-adjustment. Afterward, the result shows that every parenting style (authoritarian, authoritative, and permissive parenting style) and both coping strategies (problem-focused coping and emotion-focused coping) contributed to self-adjustment. For practical implications, any programs designed to promote positive self-adjustment among adolescents may focus on internal factors, such as coping strategy and parenting style as external factors.